Motor actions formation in 3-4-year-olds with down syndrome: efficient progress test and monitoring set - Timofeeva, I.V.; Salimov, M.I.; Repina, A.I.; Plushcheva , N.S. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop a progress test and monitoring set to track the motor skills formation process in the 3-4-year-olds diagnosed with Down syndrome. Methods and structure of the study. The progress test set was subject to an experimental study at "Sunny Children" NGO centers in the Yekaterinburg, Kamens-Uralsk, Verkhniaya Pyshma, Revda, Berezovsky and Zarechny affiliates (Sverdlovsk Oblast). We sampled for the tests the 3-4 year-olds diagnosed with Down syndrome (n=40) and concomitant diseases including minor cardiac defects and visual and hearing impairments. The kids were sampled on the family consents for the tests and personal data processing. Most common among the concomitant diseases are the cardiovascular system ones. Results and conclusion. The three-stage progress test and monitoring system makes it possible to timely find the children having specific problems/ needs in the motor skills mastering process in every group and focus the adaptive physical education instructors’ service on their developmental challenges. A special attention in the set of the motor skills development service should be paid to whether or not the child shows an interest in active games and physical exercises, with the interests rated by teachers’ monitoring in the training process. Test sessions will be run at least three times a year to fairly profile the individual motor progress. Such test and monitoring service should be designed to adequately rate the individual movement quality and controls versus the group- and age-specific standards. The monitoring and test service is commonly considered the most productive and informative progress rating method in the adaptive physical education / health service for this health group. This service will help the adaptive physical education instructor concentrate on the key aspects to timely and efficiently design and manage the service on an individualized basis. Such test and monitoring service helps analyze the adaptive physical education service benefits and drawbacks on a timely basis to attain the interim and final progress goals for success.